The effect of baking time, fillet radius, and hardness on the lifecycles of pole fastening screws in an electric motor with hydrogen embrittlement. (February 2015) - Han, HyungSuk; Lee, KyungHyun; Park, SungHo; Park, Seonghun; Song, MyongKen
Highlights: Fatigue limit of the test bolt is reduced about 8% after zinc electroplating without baking. Fatigue limit is reduced about 51% for high hardness bolt with small fillet and without baking. Baking time, hardness and fillet can affect the life reduction of bolt with hydrogen embrittlement. Abstract: In order to protect bolts from corrosion, electroplating such as zinc plating is widely used. However, hydrogen can easily penetrate or diffuse into the vacancies and dislocations between the lattices of bolt steel during electroplating. As the diffused hydrogen defects inside the lattice are in gaseous form, small cracks can easily be produced due to high pressure from the hydrogen gas. In this research, in order to determine the root cause of the fracture in pole fastening screws resulting from hydrogen embrittlement in typical electric motors, additional factors that accelerate hydrogen embrittlement fracture were selectively applied, including a small fillet in the head–shank transition and excessive hardness, and parametric study was performed experimentally.